Analisis Penerapan Strategi Customer Relationship Marketing Blibli - Lidya Melia Sari; Esis Melisa; Diratu Agnes Fitria; Tata Sutabri (International Forum of Researchers and Lecturers, 2024)
increasingly fierce business competition in the realm of e-commerce causes business people to implement the right strategy, improve service quality, and manage good relationships with consumers. Technology has changed the way businesses operate in recent decades. Rapid technological innovation has provided new opportunities for businesses to grow and develop. This needs to be done by a company as an effort to maintain loyalty customers as well as acquiring new customers. Good product quality is indeed an important factor to be able to increase company sales. However, there are other things that you should pay attention to, namely establishing good relationships with customers it is undeniable that customers are one of the factors that will affect the condition of your business. If you don't have customers, then you won't get any income. Therefore establishing a good relationship with customers becomes important for the sustainability of the company. By definition, a customer relationship is a marketing strategy that retains and manages customers to make repeat purchases. Customers that you have successfully attracted must be managed as well as possible so as not to switch to competitors. The more customers you have, the better the impact on business development. The way this is done is to manage it in such a way that it encourages purchases repetitive and prevents them from switching to competitors.this can also be done by providing answers and solutions to problems owned by customers. Customer relationship practices help salespeople automate sales activities with a customer relationship strategy, you know when to reach out to your sales prospects, what to say, and how to say it.